PENGARUH PELAKSANAAN KELAS IBU HAMIL TERHADAP PENGETAHUAN TENTANG PERSIAPAN PERSALINAN DI DESA TALAGA KECAMATAN MANCAK TAHUN 2023 - Indhawati, Wulan; Tridiyawati, Feva (LPPM Institut Pendidikan Nusantara Global, 2023)
The program organized by the Ministry of Health to support this step is the class for pregnant women. Class activities for pregnant women use learning methods, one of which is by discussing the material in the MCH book. The use of the MCH handbook is expected to improve the quality of maternal and child health and nutrition services so that one of the national development goals, namely reducing MMR and IMR, can be achieved. Based on the above, the researcher is interested in conducting research entitled